2009
DOI: 10.1111/j.1365-2125.2009.03523.x
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in the genetics of common obesity

Abstract: The genetic contribution to interindividual variation in common obesity has been estimated at 40–70%. Yet, despite a relatively high heritability, the search for obesity susceptibility genes has been an arduous task. This paper reviews recent progress made in the obesity genetics field with an emphasis on established obesity susceptibility loci identified through candidate gene as well as genome‐wide studies. For the last 15 years, candidate gene and genome‐wide linkage studies have been the two main genetic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
87
1
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(94 citation statements)
references
References 113 publications
1
87
1
5
Order By: Relevance
“…Thus, we suggest that future studies using a genomic paradigm to expose molecular regulation should employ a more mechanistic approach and focus on functions that are more directly related to the molecular alteration under investigation. This call for a careful test of functional relevance for gene-phenotype associations is in line with suggestions voiced regarding the molecular mechanism of metabolic disease (Loos 2009). We suggest that future studies of whether or how a single gene polymorphism may affect _ VO 2 max or sprint performance in different populations will most likely not advance our understanding of the underlying mechanisms that determine performance during physical exercise.…”
supporting
confidence: 62%
“…Thus, we suggest that future studies using a genomic paradigm to expose molecular regulation should employ a more mechanistic approach and focus on functions that are more directly related to the molecular alteration under investigation. This call for a careful test of functional relevance for gene-phenotype associations is in line with suggestions voiced regarding the molecular mechanism of metabolic disease (Loos 2009). We suggest that future studies of whether or how a single gene polymorphism may affect _ VO 2 max or sprint performance in different populations will most likely not advance our understanding of the underlying mechanisms that determine performance during physical exercise.…”
supporting
confidence: 62%
“…A review concerning the genetics of obesity, with an emphasis on established obesity susceptibility loci identified through candidate gene and genome-wide studies, indicated that the contribution of genetic loci to body weight increase is !2% (Loos 2009). Therefore, environmental factors, such as high saturated fat in diets, are thought to have pivotal roles in overweight and obesity (Cascio et al 2012).…”
Section: Introductionmentioning
confidence: 98%
“…The social and economic costs of obesity are high as obesity elevates the risk of several medical complications, such as type 2 diabetes (T2D), hypertension, dyslipidemia, and cardiovascular disease (Kelly et al 2008;Ogden et al 2007). More and more genetic variants associated with obesity are being discovered using candidate gene approaches, genome-wide linkage studies, and genome-wide association studies (Hebebrand et al 2010;Loos 2009). Identification of genes that contribute to risk of obesity will allow identifying individuals who are at risk, and ultimately it may lead to new therapies for treatment and prevention (Hebebrand et al 2010;Loos 2009).…”
Section: Introductionmentioning
confidence: 99%
“…More and more genetic variants associated with obesity are being discovered using candidate gene approaches, genome-wide linkage studies, and genome-wide association studies (Hebebrand et al 2010;Loos 2009). Identification of genes that contribute to risk of obesity will allow identifying individuals who are at risk, and ultimately it may lead to new therapies for treatment and prevention (Hebebrand et al 2010;Loos 2009). The search for genes that increase the susceptibility to develop obesity has become increasingly important.…”
Section: Introductionmentioning
confidence: 99%